Most accurate algorithms for RSS-based Wi-Fi indoor localisation - Fudickar, Sebastian; Valentin, M (IPIN 2014 - 2014 International Conference on Indoor Positioning and Indoor Navigation, 2014)
Since Wi-Fi transceivers are available in most handheld devices, they are well suited for indoor localisation. This article analyses the relevance of thirteen factors of modelbased received signal strength indoor-localisation algorithms on localisation accuracies and identifies for each of these factors algorithms or parameter-settings that achieve high position accuracy. In order to assure the results' meaningfulness and comparability, these factors' optima have been identified via trace-driven empirical studies. By comparing position accuracies of the optimised optLoc localisation algorithm and of the Radar algorithm, a significant increase of accuracy was shown. In case of the optLoc algorithm, error distances dropped by ca. 1m and localisation-error rates decreased also significantly. In addition, the article studies energy efficiency of Wi-Fi based indoor localisation and identifies the most energy efficient approach.